Description of Uric Acid Levels and Blood Pressure In Pulmonary Tuberculosis Patients Consuming Anti Tuberculosis Drug (ATD) in the Working Area of Sakra Public Health Center - Wahyudi, Nizar; Getas, I Wayan; Wiadnya, Ida Bagus; Srigede, Lalu (Poltekkes Kemenkes Mataram, 2023)
Background: Anti-tuberculosis (ATD) used is the standard blend of INH, PAS and streptomycin for one to two years. The amino salylic (pas) acids are then replaced with pirazinacids. Pirazinbacteria is a drug that can cause increased levels of uric acid in the body (hyacinth). Hiperurisemia is the state of concentration of the veins in the plasma or the serum has exceeded the limit of the monosodium ligament of 7.0 milligrams /dl. Hyperuricemia is also cited as an important risk factor for hypertension and other cardiovascular diseases. Research purposes: For details of uric acid and blood pressure on lung tuberculosis patients who use antituberculosis (oats) in the region of the sakra hospital. Research methods: The kind of research used I s a descriptive observation study with a sectional design, a study in which dependent and independent variables are done and measured simultaneously. The sample retrieval technique on this study USES a total sample using the criteria the researchers have chosen in selecting a sample. Research: Average uric acid and blood pressure in lung tuberculosis patients who consume single-month intensive drugs (ATD) are 7,8 mg/dl and 121/75 mmHg. Average levels of uric acid and blood pressure in lung tuberculosis patients who use 2 months of intensive phase (ATD) are 9,1 mg/dl and 129/78 mmHg. Conclusion: There are high levels of uric acid and blood pressure in those with lung TB who take anti-tuberculosis drugs (ATD).